Wacana Pelecehan Seksual Korban Laki-laki pada Film Dear David - Afiani, Devi Ilona; Suprihatin (DIGICOM : Jurnal Komunikasi dan Media, 2024)
This study aims to explore the discourse of sexual harassment against men in the film Dear David. This study uses qualitative research with the Teun A. Van Djik Critical Discourse Analysis method. The analysis was carried out at the level of text analysis, social cognition and social context. The results of this study indicate that in the text analysis, David as the victim experienced harassment both physically and verbally. This sexual harassment was also carried out by women who showed interest or liking, while highlighting that women also have sexual desires. David as the victim also experienced negative psychological impacts, namely panic attacks. In social cognition, the discourse of film production is influenced by the knowledge, awareness, and social perspectives of the production team. While in the social context, the film Dear David depicts the manipulation of power and social status as well as the phenomenon of traumatic bonding that makes it difficult for victims to report or end relationships. Power and access influence the dynamics of sexual harassment, where the concepts of toxic masculinity and victim blaming create significant social stigma that prevents male victims from reporting.